(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
This article presents some aspects of dream analysis as an important part of Daseinsanalytic therapy. Dreams are to be interpreted phenomenologically considering: 1. what phenomena appear in the dreamer’s world, and 2. how the dreamer conducts himself. To illustrate, I analyse a dream a patient told me almost two decades ago.